Pengaruh Transformasi Digital, Strategi Bisnis, dan Kesiapan Modal terhadap Keberlanjutan Usaha UMKM di Era Ekonomi Digital - Mandasari, Jayanti; Irawati, Irawati (Indo Publishing, 2026)
This research aims to analyse the influence of digital transformation, business strategies, and capital readiness on the sustainability of Micro, Small, and Medium Enterprises (MSMEs) in Sumbawa Regency in the context of the digital economy era. The acceleration of information and communication technology has demanded that MSME actors adapt by utilising digital platforms, formulating responsive business strategies, and preparing adequate capital to survive and thrive amidst increasingly dynamic market competition. The research uses a quantitative approach with the Structural Equation Modelling – Partial Least Square (SEM-PLS) method, processed through SmartPLS 3.0 software. The research sample consists of 100 respondents who are MSME actors in Sumbawa Regency, selected using purposive sampling techniques with the criteria: a minimum business age of one year, having adopted at least one form of digital transformation, and being the owner or financial manager. The analysis results show that digital transformation has a positive and significant impact on the sustainability of MSME businesses with a t-statistic value of 5.124 and a p-value of 0.000. Business strategy also proves to have a positive and significant impact on the sustainability of MSME businesses with a t-statistic of 4.867 and a p-value of 0.000. Furthermore, capital readiness has a positive and significant impact on the sustainability of MSME businesses with a t-statistic of 4.213 and a p-value of 0.000. The R-Square value of 0.684 indicates that 68.4% of the variability in MSME business sustainability can be explained by these three independent variables. These findings provide a theoretical contribution to the development of MSME management literature as well as practical implications for business actors and local governments in formulating holistic and sustainable digital-based MSME support policies.